Casebook in Abnormal Psychology - Vitkus J. (New York St. Louis San Francisco Auckland McGraw-Hill, Inc., 1993)
This casebook accompanies "Abnormal Psychology, 6/e", by Bootzin, Acocella and Alloy. By presenting case studies from actual practitioners, it illustrates how psychologists diagnose and treat various psychological disorders. Written in an accessible style, it aims to maintain a solid balance between scientific vigour and readability, and it presents a diverse selection of interesting and vivid cases from a variety of theoretical viewpoints. Seven new cases have been added, making a total of 18, and each case is organized into five sections: presenting complaints, personal history, conceptualization and treatment, prognosis, and discussion.
Keywords: 159.9